KULTIVASI SPIRULINA PLATENSIS PADA MEDIA BERNUTRISI LIMBAH CAIR TAHU DAN SINTETIK (Jurnal Bahan Alam Terbarukan, 2016)
This research was conducted to study the effect of various additions of synthetic nutrient into Spirulina platensis growth medium containing tofu wastewater 8%v/v. Synthetic nutrient was varied at 50, 75, 100%. Based on abservation, the OD680 (Optical Density at 680 nm) increased until in the end of cultivation time with final OD680 of 0.381, 0.392, 0.189 for variable of 50, 75, 100% respectively. Meanwhile, the growth rate value was 0.0743, 0.0759, 0.0354/day. The best protein content was obtained at nutrient synthetic of 75%, which was 91,27%. The good growth and protein content of S. platensis obtained at nutrient synthetic of 75%, which had C:N:P ratio of 128:12:1.